PELAKSANAAN METODE DISKUSI KELOMPOK TERHADAP MOTIVASI BELAJAR SISWA KELAS V DI MI MIFTAHUL ULUM - Rantika Miranti; Roaisyah, Eka; Adi Saputra, Chandra; Pangastuti, Diana; Yuliani, Ririn; Syarnubi, Syarnubi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
Basically a teacher is an educator. Educators are adults with all the abilities they have to be able to change the psychic and mindset of their students from not knowing to knowing and maturing their students. Thus the teacher must apply learning methods that are in accordance with the characteristics of their students including Using one of the group discussion methods, where this method is used by the teacher to encourage the process of involving two or more people Participants interact with each other (exchange opinions), or defend each other's opinions in problem solving so that agreement is obtained between them. The use of discussion methods carried out during classroom learning shows that these methods are able to help students to build and improve their ability to express their opinions. Schools as formal educational institutions have a very important role in educating and maturing students through the learning process. In learning there are several factors that affect the teaching and learning process and student learning outcomes, one of which is learning motivation, motivation is the basis for students to be able to obtain maximum learning results, where further learning results will be used as a basis for determining the expected achievement of competencies